Facial paralysis in feedlot cattle associated with otitis caused by Mycoplasma bovis: first report in Argentina - Margineda, Carlos A.; Diab, Santiago; Quiroga, María Alejandra; López, Alfonso (Brazilian Journal of Veterinary Pathology, 2023)
The paper describes an outbreak of Mycoplasma bovis-associated bronchopneumonia and otitis clinically associated with facial paralysis in feedlot steers in Argentina. Three of sixty-one feedlot animals from the same pen developed unilateral facial paralysis primarily with ear dropping, droopy eyelids (eyelid ptosis), and head tilt. Postmortem exanimation revealed cranioventral consolidation of the lungs (bronchopneumonia) and the presence of abundant purulent exudate in the tympanic bulla (otitis). The affected lung had a nodular appearance. Histopathological examination of the middle and inner ear showed necrotizing, suppurative otitis, and bronchopneumonia with bronquiectasis compatible with M. bovis infection. Immunohistochemistry of the lung, and middle and inner ear revealed abundant M. bovis antigen. The ELISA tests revealed that the two animals showing facial paralysis had seroconverted for M. bovis. To our knowledge, these are the first reported cases of M. bovis otitis in Argentina. These findings should alert veterinarians and diagnosticians of the relevance of M. bovis as a cause of otitis and facial paralysis in cattle.